KARAKTERISTIK PENDERITA HIPERTENSI DENGAN KOMPLIKASI STROKE DI RSUP H. ADAM MALIK TAHUN 2014-2016 - Ribka Valentina S; Jemadi .; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
In Indonesia, the percentage of adults with hypertension increased from 8% in 1995 to 32% in 2008. Hypertension is a major risk factor for cardiovascular disease and stroke. The research was conducted to know the characteristic of hypertension patient with stroke complication at Rumah Sakit Umum Pusat Haji Adam Malik Medan.                The research method is descriptive research with case series design. The population of all patients with hypertension with stroke complication 2014-2016 as many as 113 people.                     The result from this study obtained that the highest proportion of hypertension patient with stroke complication is in the age group 55-59 years old (28,3%), male gender (51,3%), Bataknese (61,1%), Islam (51,3%), entrepreneurs (27.5%), married (79,6%), lives outside of Medan city (72,6%), hypertension stage 2 (72,6%), hemorrhagic stroke (85,0%), normal body mass index (22,1%), no other complications (50,4%), died (45,1%). There is no difference of the age based on the stage of hypertension (p=0,356), type of stroke (p=0,323), gender based on stage of hypertension (p=0,193), type of stroke (p=0,702), type of stroke based on stage of hypertension (p=0,431), stage of hypertension based on body mass index (p=0,748), there is difference between type of stroke and the coming home condition (p=0,002).               Recommended to people at risk of hypertension to routinely check blood pressure and make a healthy lifestyle. To people with hypertension to do regular control and take medication regularly and do a healthy lifestyle to prevent the occurrence of complications.  Keywords: Hypertension, Stroke, Characteristics